KEEPING ON THE PATH IN FIVE POEMS BY ALICE WALKER - Ririn Rosada; Kurnia Ningsih (Universitas Negeri Padang, 2019)
This article is about the analysis of five poems by Alice Walker entitled Blessed Are The Poor In Spirit(BATPIS), If I was President(IIP), To Change The World Enough(TCTHE), Working Class Hero(WCH), You Want To Grow Old Like The Carter(YWTGOLTC)focuses on how the black woman who is represented by the speaker maintains her movement for a better life. The problem of this analysis is how far these poems exposes about the efforts of the speaker to get the position in the public area. The purpose of the analysis is to find out the way of the speaker to survive and achieve her goal. This analysis is involved the elements of poetry such as irony, imagery, tone and the speaker to reveal the issue of keeping on the path in these poems. This analysis is related to the concept of feminism by Bell Hooks. The result of this analysis shows that the speaker is able to keeping on the path for a better life .